The acceptability of the concept of a multipurpose cooperative in Brgy. Mambatad, Miag-ao, Iloilo. - Reyes, Ariel L
This study stems from the hypothesis that cognitive and behavioral acceptance of a developmental concept is dependent on socio-economic factors in the community. With the introduction of the concept, the respondents form positive or negative attitudes toward it. A survey was conducted to find out the relationship between Barangay Mambatad residents' social and demographic characteristics and the acceptance of the concept of a Multipurpose cooperative. , The study demonstrates how demographic and social variables affect the acceptability of the concept of a multipurpose cooperative. The descriptive design validates the respondents attitudes obtained through a Likert scale. To further determine the relationship of the variables to acceptance, the Chi-square, Pearson Product-moment and Spearman Rank correlation tests were applied. Other factors and conditions relevant to the promotion of a multipurpose cooperative in the community were also investigated and analyzed. Despite the very limited knowledge of the respondents on cooperatives, the study concludes the acceptance is independent of demographic and social variables. The correlation tests show that `educational attainment', `position in the community organizations', `awareness of cooperatives' are the only variables which have any direct relation to acceptability. This indicates that higher education, position and increased awareness greatly contribute to acceptance.Even with various experiences on cooperative education and the respondents exposure to cooperative organizing, it is evident that in order to make any community project sustainable it is necessary for not only initial but also continuous acceptance.